"Right on the money": CBE student satisfaction and postgraduation outcomes. Issue 2 (18th April 2017) - Rivers, Carlos; Sebesta, Judith A.
Abstract : Background: A review of existing research on CBE program outcomes provides context for the research focus of the essay. Method: This essay analyzes results from a comparative study of surveys of graduates of both a competency‐based education program at Texas A&M University‐Commerce and its traditional counterpart at the same institution in order to assess both student satisfaction with the degree programs and postcompletion outcomes. Results: A narrative and visual description of key findings from the survey results reveal three areas of focus—faculty/staff interaction, affordability/acceleration, and alumni outcomes. Conclusion: The results suggest augmented outcomes for the CBE program compared to its traditional counterpart, contributing to a better understanding of student satisfaction and postcompletion outcomes for students who have graduated from a CBE program relative to a traditional program.